RANCANG BANGUN APLIKASI MONITORING DAN TRACKING BUS TRANS KOETARADJA BERBASIS ANDROID - Devi Mulia Sari; Safwan; Muhammad Ilham (Politeknik Aceh, 2017)
Bus Tracking is an application that tracks bus position. Tracking System involves the installed Android App on smartphone. The application is built for bus and user. On the application, the map shows the bus location and provide the actual information to the users in different time interval. The server will store the data in the firebase database. Since it is real-time system, it automatically sends the information from the smartphone to the othersmartphones.